The da Vinci Xi Robotic Four-Arm Approach for Robotic-Assisted Minimally Invasive Esophagectomy - Grimminger, Peter Philipp; Hadzijusufovic, Edin; Ruurda, Jelle Piet-Hein; Lang, Hauke; van Hillegersberg, Richard (The Thoracic and Cardiovascular Surgeon, 2018)
Robotic surgery is gaining importance in complex thoracoscopic surgery, such as robotic-assisted minimally invasive esophagectomy (RAMIE). The RAMIE procedure was designed using the first generation of the robotic system. The latest da Vinci Xi system has substantially increased the dexterity, especially designed for multiquadrant surgery. The original three-arm RAMIE approach was modified including the robotic four-arm use for the thoracoscopic and laparoscopic part of the operation. This extended approach (four-arm RAMIE approach) provides more flexibility and raises the independence of the surgeon.
Keywords: da Vinci Xi; RAMIE4; esophageal cancer; MIE; RAMIE